Problems and achievements of the country's first mathematics contest of the pupils of fourth form - Kiseliova, Danutė; Kiseliovas, Arkadijus (Lietuvos matematikos rinkinys, 1999)
In the article the achievement, results and problems of the Country's first contest of the pupils of fourths form have been presented and analysed.